Implementasi Metode Pembelajaran Diskusi Kelompok untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar Siswa - Rus, Aipan; Fatmawati, Ani; Muliadi, Agus (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
The purpose of this study was to improve science process skills and cognitive learning outcomes of class XI students of Middle 1 Praya Middle school year 2017/2018. The subject of this study were 31 students of class XI IPA-3 Praya Tengah as many as 31 people. This type of research is classroom action research conducted in two cycles. Data collection techniques used observation techniques for the implementation of learning, and tests as many as 20 questions. The results of the learning implementation observation in the first cycle = 41% and in the second cycle was 66%. Cognitive learning outcomes of students reach an average in the first cycle of 56.6 with classical completeness of 38.70% and experienced an increase in the second cycle with an average of 64.35 with classical completeness of 54.83%. Thus, the method of group discussion can improve science process skills and cognitive learning outcomes of class XI Middle Praya 1 Middle School 2017/2018 academic year.